SIGNS BEYOND: A SEMIOTIC READING OF TRANSCENDENCE IN “STUCK IN THE MIDDLE” BY BABYMONSTER - Muliawan, Anugrah Adi; Darmanto, Darmanto; Hakim, Luqman; Dewi, Ekka Zahra Puspita; Cahyo, Eko Nur (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study explores the representation of transcendental themes in the music video Stuck in the Middle by K-pop girl group BABYMONSTER using Charles Sanders Peirce’s semiotic framework. Through qualitative analysis, six visually rich scenes were examined to uncover how signs—icons, indexes, and symbols—convey deeper meanings related to self-reflection, emotional isolation, aspiration, and the human connection with the cosmos. The research finds that visual elements such as cosmic landscapes, symbolic colors, lighting contrasts, and fantasy-inspired settings serve as metaphors for emotional and spiritual journeys. These scenes construct a layered narrative that combines fantasy aesthetics with existential themes, reinforcing K-pop’s capacity to deliver profound messages beyond entertainment. By analyzing these transcendental signifiers, the study highlights the role of visual semiotics in shaping the cultural and philosophical depth of Korean popular music in a global context.